Isolating a cerebellar contribution to rapid visual attention using transcranial magnetic stimulation - Arasanz, Carla P.; Staines, W. R.; Schweizer, Tom A. (Frontiers in Behavioral Neuroscience, 2012)
Patient and neuroimaging research have provided increasing support for a role of the posterior-lateral cerebellum in cognition, particularly attention. During rapid serial visual presentation, when two targets are presented in close temporal proximity (<500ms), accuracy at detecting the second target (T2) suffers. This phenomenon is known as the Attentional Blink (AB), and in cerebellar lesion patients this effect is exaggerated. Damage to the cerebellum may thus disrupt the use of attentional resources during stimulus processing conditions that are temporally demanding. There are reciprocal connections between the cerebral cortex and the contralateral cerebellum, these connections allow for the possibility that lateralized functions in the cerebral cortex (such as language) remain lateralized in the cerebellum. The purpose of this study was to investigate the temporal characteristics of the cerebellar contribution to the AB and to functionally localize the contribution of the cerebellum to the AB using transcranial magnetic stimulation (TMS). We hypothesized that T2 accuracy would decrease after right cerebellar stimulation when the delay between the first and second target was short (120-400 ms) compared to long (720-960 ms). We used continuous theta burst stimulation (cTBS), a form of TMS, to transiently inhibit a focal population of neurons in the left and right posterior-lateral cerebellum of healthy participants (n=45). Three groups of participants (n=15) performed the AB before and after either sham, left, or right cerebellar stimulation. The results of this cTBS study support our hypothesis. During the short delay, participants in the right cTBS group showed a greater AB magnitude compared to both the left and sham cTBS groups (p< 0.05). No difference in T2 detection was found over long delays. The results provide further support for a cerebellar contribution to an integrated neural network recruited during temporally demanding attention-based tasks.